The Dynamics of Framing Environmental Values and Policy: Four Models of Societal Processes. (1st May 2000) - Miller, C.A.
Abstract : While the subject of framing has achieved considerable recognition recently among social scientists and policy analysts, less attention has been given to how societies arrive at stable, collective frames of meaning for environmental values and policy. This paper proposes four models of societal processes by which framing occurs: narration, modelling, canonisation and normalisation. These four models are developed, compared, and explored in detail through a case study of the framing of the impacts of climate change on human societies in US science policy from the 1960s through the 1990s. I conclude by offering a number of potentially fruitful avenues for further research into the dynamics of framing.